Design of a GSM Based Energy Meter Monitoring and Tamper Detection System. - Bakenge Joshua (Kabale University, 2023)
Energy theft continues to be an issue of great challenge for electricity operators all over the world today. The attempt to detect and reduce the energy theft mechanisms is a challenging task due to insufficient inspection methods. With the evolution of smart and advanced metering infrastructure (AMI), a more complicated status quo in energy theft emerges and therefore new technologies have to be adopted to solve the problem. In order to adopt new technological advancements to cipher some of the recurring irregularities on the energy grid, in this project, a low voltage energy meter monitoring system with tamper proof measures using GSM technology is proposed. When fully adopted and implemented by the different Electricity Regulatory bodies, consumer meter monitoring can be achieved. The project proposes the ability to monitor real time consumer power usage, meter tampering, consumer ability to interact with the system, and adoption of GSM technology in LV metering units. This will improve transparency between the electrical service provider and the consumer and will greatly reduce on the non-technical energy losses on the electrical grid in many developing countries. The project therefore predicts encouraging results in residential consumers’ power monitoring and theft detection that will help utilities to improve the reliability, security and operation of the power network.